WRITING CENTERS: THEORY AND ADMINISTRATION (Editor: Gary A. Olson) - Speyer, Elizabeth C. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1986)
Gary A. Olson, Editor. WRITING CENTERS: THEORY AND ADMINISTRATION. Illinois: National Council of Teachers of English, 1984 247 pp. 15.50